In Situ Observation of the Thermal Behavior of Graphene on Insulating and Metal Substrates - Mikihiro Kato; Xinwei Zhao (Nanomaterials)
In general, graphene is known to be thermally stable. In this study, we analyzed the Raman spectra of graphene prepared on copper (Cu) and nickel (Ni) by chemical vapor deposition (CVD) as well as monolayer and multilayer graphene transferred onto SiO2 under vacuum heating. We observed a shift in the position of the graphene G peak due to temperature changes for all substrates. For graphene on insulating substrates, the peak position returned to its original position after heating when the substrate returned to room temperature, indicating the thermal and chemical stability of graphene. In contrast, the Raman spectra of graphene on Cu and Ni, which have different carbon solubilities, showed significant shifts and broadening of the G peak as the temperature increased. We also utilized optical microscopy to observe morphological changes during heating, which complemented the Raman spectroscopy analysis. The optical microscopy images obtained in the previous study revealed morphological changes on the graphene surface that correlate with the shifts observed in the Raman spectra, especially in graphene on metal substrates. These combined findings from Raman spectroscopy and optical microscopy could provide insights for optimizing graphene growth processes. In addition, knowledge of the thermal behavior of graphene on insulating substrates could be useful for device construction.